Role of Hypoalbuminemia as an Independent Predictor of 30-Day Postoperative Complications Following Surgical Fixation of Ankle Fractures. (March 2020) - Wilson, Jacob M.; Kukowski, Nathan R.; Staley, Christopher A.; Bariteau, Jason T.
Background: Malnutrition is known to be negatively associated with outcomes after multiple orthopedic procedures. We hypothesized that admission albumin levels, as a marker for malnutrition, would correlate with postoperative outcomes. The purpose of this study was to investigate this relationship following surgery for ankle fracture. Methods: This is a retrospective cohort study of the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database. Patients undergoing operative fixation of an ankle fracture were identified. A total of 6138 patients with albumin available for analysis were identified. Baseline patient information, preoperative serum albumin levels, 30-day postoperative complications, readmission, reoperation, and length of stay data were then collected. Poisson regression with robust error variance was performed to assess the effect of preoperative serum albumin level on postoperative outcomes. Results: The mean albumin level was 3.86 g/dL and 20.3% (1246/6138) of patients with available albumin levels were hypoalbuminemic. Multivariate analysis revealed that an albumin level <3.5 g/dL was an independent risk factor for complications (relative risk [RR], 1.42; 95% confidence interval [CI], 1.13-1.78; P = .002) and readmission (RR, 1.54; 95% CI, 1.13-2.08; P = .006). Additionally, when analyzed as a continuous variable, albumin level was negatively correlated with risk of mortality (RR, 0.37; 95% CI, 0.19-0.72; P = .003). Patients with hypoalbuminemia also had significantly longer lengths of stay (4.5 vs 2.1 days; P < .001). Conclusion: While complication rates after fixation of ankle fractures remain low, hypoalbuminemia was a predictor of postoperative course. Malnutrition, therefore, may help inform the decision between surgical and conservative management of patients with ankle fractures potentially amenable to nonoperative management. Additionally, hypoalbuminemia should trigger heightened awareness and prophylactic therapy where appropriate. Level of Evidence: Level III, comparative study.